Classe ouvrière et social-démocratie : Lille et Marseille. - Bleitrach, Danielle; Lojkine, Jean; Oary, Ernest; Delacroix, Roland; Mahieu, Christian (Paris : Editions Sociales, 1981)
Bibliotheek François Vercammen
Frans
Monografie